PELAKSANAAN PENERAPAN DENDA TILANG BAGI PELANGGAR LALU LINTAS MENURUT UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI PENGADILAN NEGERI PEKANBARU - Z, Riduan; Haryono, Dodi; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Traffic violations often occur in various places, not just in Pekanbaru, but almost in all regions of Indonesia, Act No. 22 of 2009 about traffic and road transport, in the implementation of the final cost is still not running optimally, it is related to traffic offences, for example not to wear a helmet, or not using a seat belt that occur in everyday life. Results achieved in this study that in the application of fines speeding tickets for traffic violations and Court in your State road transport Soweto according to Act No. 22 of 2009 about traffic and road transport, is still not running optimally, the reality of the situation in the application of fines speeding tickets do not seseuai with the existing legislation, although Act No. 22 has long been enacted, for example someone who got speeding tickets by Polantas because it does not carry a license plate Number of the vehicle (VEHICLE REGISTRATION) If following the law number 22 Years 2009 should he pay a fine of Rp 250,000, a speeding ticket but after following the trial only Rp. 50.000,-for two wheels, four wheels as for Rp 80,000,-and a six-wheel for over 100,000, application of fines tilang differences that now the District Court in pekanbaru, skyrocket by economic, that is not yet ready will cost fines so great for diterapan, so that the State Court judge pekanbaru in deciding fines speeding tickets is still not in accordance with the legislation Number 22 in 2009 about traffic and roads.